Bagaimana Budaya Kerja Berpengaruh Terhadap Kinerja Pegawai Di Kabupaten Garut - Yusup Hermawan; Nurbudiwati Nurbudiwati; Iwan Setiawan (Jurnal Pembangunan dan Kebijakan Publik (JPKP), 2020)
The background of this study is the phenomenon of low employee performance caused by work culture that is not yet optimal in the Regional Coordinator of Education in Karangpawitan District, Garut Regency. The purpose of this study is to find data and information regarding the magnitude of the influence of work culture on employee performance in the Regional Coordinator for Education in the Karangpawitan District, Garut Regency. Its purpose is to increase knowledge in the field of State Administration, especially regarding work culture and employee performance. This research uses descriptive survey method. The author took the location of the study in the Regional Education Coordinator in Karangpawitan District, Garut Regency, involving employees and principals in the Karangpawitan District Education Sector Coordinator in Garut Regency with a total sample of 48 respondents, using proportional employee sampling techniques. From the results of data analysis states that the responses of respondents to the implementation of the average workforce choose alternative answers to good criteria. While the respondents' responses to the average employee performance variable chose alternative answers to good criteria. The results of data processing with quantitative analysis, the Spearman correlation coefficient is 0.55265, the t-test is 5.60407 and the t-table is 1.67866. So the proposed hypothesis is accepted, or there is an influence of work culture on employee performance in the Regional Coordinator in the Field of Education in Karangpawitan District, Garut Regency in Karangpawitan District, Garut Regency because of t-count> t-table. With a coefficient of determination (influence) of 31%.